Using Video in Research and Documentation: Ethical and Intellectual Property Issues to Consider- Fact Sheet - Intellectual Property Issues in Cultural Heritage; Jane Anderson; Kelly Bannister; Emma Feltes; Ellen Frankenstein; Kate Hennessy; Julie Hollowell; Jock Langford; Silke von Lewinski; Douglas Trainor (Simon Fraser University, 2013)
The IPinCH Fact Sheet initiative aims to provide information and guidance on important issues emerging in cultural heritage research. RESOURCESDeclarationsReportsPublicationsPresentationsVideosPodcastsFact SheetsTeaching ResourcesReading ListsLinks